Identification of peptides from camel milk that inhibit starch digestion. (June 2023) - Althnaibat, Rami M.; Bruce, Heather L.; Gӓnzle, Michael G.
Abstract: The inhibition of starch digestion activities by peptides derived from camel milk proteins was determined and the effect of their amino acids charge and/or hydrophobicity was assessed. Starch digestion by pancreatic and brush border enzymes was assessed in vitro with a peptide to starch ratio of 1:3 (w/w). Hydrolysed whey proteins were more inhibitory than hydrolysed casein. Successive chromatographic separation of peptides enriched positively charged peptides with hydrophobic amino acids. Whey protein hydrolysate inhibited starch hydrolysis by 16%; peptide fractions recovered after CEX and HIC inhibited starch hydrolysis by 33–36%. Peptides in the active fractions were identified by LC–MS/MS and the inhibitory activity of 6 synthetic peptides was evaluated. Two of these six peptides, LALDIEIATYR and VLDELTLAR, inhibited starch hydrolysis by 34–37%. In conclusion, specific peptides that are produced before or during in vitro digestion can inhibit starch digestion and may moderate postprandial blood glucose levels in vivo.